5(x+10)+3(-x+8)=-10

Simple and best practice solution for 5(x+10)+3(-x+8)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+10)+3(-x+8)=-10 equation:


Simplifying
5(x + 10) + 3(-1x + 8) = -10

Reorder the terms:
5(10 + x) + 3(-1x + 8) = -10
(10 * 5 + x * 5) + 3(-1x + 8) = -10
(50 + 5x) + 3(-1x + 8) = -10

Reorder the terms:
50 + 5x + 3(8 + -1x) = -10
50 + 5x + (8 * 3 + -1x * 3) = -10
50 + 5x + (24 + -3x) = -10

Reorder the terms:
50 + 24 + 5x + -3x = -10

Combine like terms: 50 + 24 = 74
74 + 5x + -3x = -10

Combine like terms: 5x + -3x = 2x
74 + 2x = -10

Solving
74 + 2x = -10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-74' to each side of the equation.
74 + -74 + 2x = -10 + -74

Combine like terms: 74 + -74 = 0
0 + 2x = -10 + -74
2x = -10 + -74

Combine like terms: -10 + -74 = -84
2x = -84

Divide each side by '2'.
x = -42

Simplifying
x = -42

See similar equations:

| d-86/=4 | | 3a+(6a^2)= | | x+1=4x-20 | | 5+3x=2(-x+6)-22 | | 16=19-3w | | x=0.0048x^3-0.0054x^2+0.157x+1.91 | | x-10+2x-10=46 | | 4(x-5)=x+13 | | 9x-7=x+33 | | 10=1.4x+0.8y | | x=0.0048x^3-0.0054x^2 | | 7+2u=15 | | 1/2x-1/3=5/2 | | 3x+18=5x+14 | | 3x+2(-2x-4)=-4 | | 30x+40=7x+34 | | 3x-7=x+41 | | 4(3x+2)-x=8x-8 | | 7(g-3)+5g= | | 3=4x^(2/5) | | h-6u+7=-29 | | 6=2k-8k | | E(x)=0.0048x^3-0.0054x^2 | | 7(x-6)=5(x+2) | | 6b^2=42b-72 | | 7(8-9x)=0 | | 3x+9-5x+7-2x=20 | | 7y+45=y-3 | | -x+21=x+9 | | a-17=48 | | 3b-3=9 | | (4x+8)-(2x+4)=2x |

Equations solver categories